PANJI TRADITION IN THE JARANAN JOR AND WAYANG TIMPLONG PERFORMANCE ARTS IN EAST JAVA - Trisna Kumala Satya Dewi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
The people of East Java are still familiar with Panji tradition as their collectivememory. Panji tradition is actualized in the form of art performances, such as JarananJor (Blitar) and Wayang Timplong (Nganjuk). Jaranan Jor and Wayang Timplong arestill often performed for various purposes which mean that both are still functional insociety. This paper aims to reveal the Panji tradition in performing arts in East Java,especially Jaranan Jor (Blitar) and Wayang Timplong (Nganjuk). It also tries to reveal ashift of the function of both performances based on their actualization in today'ssociety. Jaranan Jor has changed its function in society, from the function of ritualceremonies into entertainment (spectacle) function. Wayang Timplong is stillfunctioning as a ritual ceremony of Nyadran (village cleaning). However, WayangTimplong also serves as entertainment as well as various social communal activitiessuch as marriage, circumcision, nadar etc.